2002
DOI: 10.1002/hyp.1084
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the relationship between catchment vegetation type and the variability of annual runoff

Abstract: Abstract:The impact of changing catchment vegetation type on mean annual runoff has been known for some time, however, the impact on the variability of annual runoff has been established only recently. Differences in annual actual evapotranspiration between vegetation types and the potential effect of changing vegetation type on mean annual runoff and the variability of annual runoff are briefly reviewed. The magnitude of any change in the variability of annual runoff owing to a change in catchment vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The three dominant climate types are tropical Aw ('wet-dry tropics') 1 In this context, RoW incorporates rivers from all continents excluding those located in Australia and southern Africa (defined as south of the equator). The division between Australia plus southern Africa and the rest of the world is based on analysis of annual streamflows characteristics by Finlayson, McMahon and Peel over the past 20 years using a global streamflow dataset initially collated by McMahon during the 1980s and revised and supplemented over time McMahon, 1977;McMahon et al, 1987McMahon et al, , 1992Peel et al, 2001Peel et al, , 2002aPeel et al, , 2004a.…”
Section: Climate Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The three dominant climate types are tropical Aw ('wet-dry tropics') 1 In this context, RoW incorporates rivers from all continents excluding those located in Australia and southern Africa (defined as south of the equator). The division between Australia plus southern Africa and the rest of the world is based on analysis of annual streamflows characteristics by Finlayson, McMahon and Peel over the past 20 years using a global streamflow dataset initially collated by McMahon during the 1980s and revised and supplemented over time McMahon, 1977;McMahon et al, 1987McMahon et al, , 1992Peel et al, 2001Peel et al, , 2002aPeel et al, , 2004a.…”
Section: Climate Classificationmentioning
confidence: 99%
“…The applicability of results from continental scale analysis of Australian and global streamflow datasets to northern Australia is limited by a lack of flow data for this region (e.g. McMahon, 1977McMahon, , 1982McMahon et al, 1987McMahon et al, , 1992Haines et al, 1988;Finlayson and McMahon, 1992;Dettinger and Diaz, 2000;Peel et al, 2001Peel et al, , 2002aPeel et al, , 2004a.…”
Section: Introductionmentioning
confidence: 97%
“…Firstly, there have been a number of papers highlighting the hydrologic differences between ASA and RoW and discussing the reasons for the differences (McMahon et al, 1992;Peel et al, 2001;Peel et al, 2002;Peel et al, 2004a). With this enhanced data set, we wish to review these results and evaluate them more fully.…”
Section: Introductionmentioning
confidence: 96%
“…Peel et al (2001) confirmed these results using an improved and expanded annual runoff database and suggested that the continental differences in the variability of annual runoff were primarily caused by continental differences in the variability of annual precipitation and the spatial distribution of evergreen and deciduous vegetation in temperate regions. The role of evergreen and deciduous vegetation in modifying the variability of annual runoff at a station is limited by mean annual precipitation, the seasonality of precipitation (Peel et al, 2001) and potentially by the proportion of forested catchment area (Peel et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%